A Study on Gen Z Consumer Attitudes Towards OTT (Over-the-Top) Platforms in India and Its Impact on Online Piracy - Moochhala, Quresh (Digital Repository of Theses - SSBM Geneva, 2025)
This thesis examines Generation Z’s attitudes toward Over-the-Top (OTT) platforms in India and their role in online piracy, based on a quantitative survey of 1000 respondents conducted from December 2024 to January 2025. The study meets five objectives: identifying OTT preference drivers, uncovering piracy motivations, applying the Theory of Planned Behaviour (TPB) and Social Learning Theory (SLT), and pinpointing factors driving OTT piracy. Results reveal JioCinema and Netflix as favoured platforms due to cost and content variety, yet piracy thrives among 16-19-year-olds and college students, driven by Fear of Missing Out (FOMO), limited content availability, social influence, and easy internet access via VPNs. Hypotheses linking piracy to FOMO, low legal awareness, and content scarcity were strongly supported, with TPB highlighting social norms and weak perceived control, and SLT highlighting peer reinforcement and accessible technology. While platform preference showed a weak direct link to piracy, unavailable content and peer-driven motives emerged as dominant forces. These findings align with prior research. Eight recommendations emerged which covered affordable subscriptions, synchronized releases, and awareness campaigns—target Gen Z’s tech-savvy piracy habits. Limited by an urban focus and pre-merger data gaps, the study suggests future rural and longitudinal research. Bridging theory and practice, it provides Indian OTT providers and policymakers actionable strategies to curb piracy in India’s evolving media landscape.